Everting the Theatrical Sphere Like Terayama - Ridgely, Steven (Performance Matters, 2024)
This essay attempts to understand humanistic performances through STEM fields, specifically engaging with Terayama Shūji’s 1970s avant-garde theatre and film through the study of topology. The mathematical transformation called eversion is posited as frame for Terayama’s multiple radical reversals, moving toward residual effects, a process that holds the potential for radically other performance to alter the experience of time and space. Performances of bodily intervention evert the form of theatre and elicit frustration and other affective states that generate a “transformation of theatricalized space.” The essay studies Terayama Shūji’s interest in mathematical models of eversion, or turning the inside out, and how these have influenced his work in avant-garde theatre and film, positioning the audience beyond the mere notion of “revolution” into something more complex and evocative, in which the highly scripted expectation of normative everyday life comes into question. Bodily and spatial interventions bring together viewers and performers with the purpose of transforming social life through the affects—the everting—of the particular feelings generated by the experience of the artwork.